Understanding Message Distortion In Tiktok Media Exposure - Diaz, Marianus; Pawito; Noevi Rahmanto, Andre (PT FORMOSA CENDEKIA GLOBAL, 2024)
This qualitative research examines and explains the phenomenon of delivering messages in the TikTok application. There are consequences for changing the meaning of the message after a message is delivered through. The study used Harold Lasswell's concept of communication, which was linked to James Coleman's rational choice theory. This study aims to explain the essence of the message to the TikTok community. Researchers use Harold Lasswell's communication component to explain this phenomenon because TikTok is a mass communication medium. The results found that distorted messages occurred due to information sharing on the same thing. The TikTok community took over the same message and transmitted it as a new video. It was also found that the purpose of communication on TikTok is not only to convey a message but also to convey or receive the same feelings from the messenger. That is why TikTok has become an addiction for its users.